2023
DOI: 10.1126/scitranslmed.abn5993
|View full text |Cite
|
Sign up to set email alerts
|

Anti-merozoite antibodies induce natural killer cell effector function and are associated with immunity against malaria

Abstract: Natural killer (NK) cells are potent immune effectors that can be activated via antibody-mediated Fc receptor engagement. Using multiparameter flow cytometry, we found that NK cells degranulate and release IFN-γ upon stimulation with antibody-opsonized Plasmodium falciparum merozoites. Antibody-dependent NK (Ab-NK) activity was largely strain transcending and enhanced invasion inhibition into erythrocytes. Ab-NK was associated with the successful control of parasitemia after experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 64 publications
(138 reference statements)
1
18
0
Order By: Relevance
“…The level of NK cell degranulation in variant V1 was comparable to that of MSP1. This activity has been recently demonstrated to be an important mechanism of action of antibodies in malaria in the context of both naturally acquired immunity and vaccine studies (35,60,61) We detected extensive variation in the serological responses to the 27 common variants of ARMA identified in African isolates. This level of diversity was remarkable given that there were only 1 -4 amino acid differences between variants.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The level of NK cell degranulation in variant V1 was comparable to that of MSP1. This activity has been recently demonstrated to be an important mechanism of action of antibodies in malaria in the context of both naturally acquired immunity and vaccine studies (35,60,61) We detected extensive variation in the serological responses to the 27 common variants of ARMA identified in African isolates. This level of diversity was remarkable given that there were only 1 -4 amino acid differences between variants.…”
Section: Discussionmentioning
confidence: 76%
“…This experiment was performed using a protocol that was recently developed in our laboratory (35). Briefly, following coating 30 ng/ml recombinant proteins; V1, V2 and MSP1 (control), in 96-well culture plate at 4°C overnight, the wells were washed with PBS and blocked for 2 hours at 37°C with 1% casein in PBS.…”
Section: Functional Antibody Assays Nk Cell Degranulation Assaymentioning
confidence: 99%
“…It is widely accepted that antibodies play a key role in antimalarial immunity ( Cohen et al, 1961 ; Sabchareon et al, 1991 ) and emerging data highlight the importance of Fc-mediated effector functions for a protective immune response. This includes the recruitment of complement factors ( Boyle et al, 2015 ; Reiling et al, 2019 ) natural killer (NK) cells ( Odera et al, 2023 ), monocytes ( Hill et al, 2013 ; Osier et al, 2014 ; Musasia et al, 2022 ), and neutrophils ( Joos et al, 2010 ). We recently conducted a controlled human malaria infection study in semi-immune Kenyan adults (CHMI-SIKA) ( Kapulu et al, 2022 ) where we showed that antibody-dependent phagocytosis of ring-stage parasites ( Musasia et al, 2022 ) and activity of NK cells against merozoites ( Odera et al, 2023 ) were important functional correlates of protection.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the recruitment of complement factors ( Boyle et al, 2015 ; Reiling et al, 2019 ) natural killer (NK) cells ( Odera et al, 2023 ), monocytes ( Hill et al, 2013 ; Osier et al, 2014 ; Musasia et al, 2022 ), and neutrophils ( Joos et al, 2010 ). We recently conducted a controlled human malaria infection study in semi-immune Kenyan adults (CHMI-SIKA) ( Kapulu et al, 2022 ) where we showed that antibody-dependent phagocytosis of ring-stage parasites ( Musasia et al, 2022 ) and activity of NK cells against merozoites ( Odera et al, 2023 ) were important functional correlates of protection. Furthermore, additional analyses incorporating the full-panel of Fc-dependent and non-Fc mechanisms revealed that the breadth of effector functions targeting merozoites was most strongly associated with protection.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, γδ T-cells producing proin ammatory cytokines in response to PfRBC have been linked to protection from parasitaemia (32). Secondly, these innate immune cells directly mediate cellular cytotoxicity against PfRBC, involving release of granzymes and granulysin by degranulation upon exposure to merozoites and PfRBC (33)(34)(35)(36)(37)(38)(39)(40). γδ T-cells and NK are directly activated by PfRBC components (27,29,33,34,(41)(42)(43)(44): via phosphoantigens recognized by γδ T-cells (42,43), and NK sensing of host Hsp70 expression on PfRBC (33), recognition of PfEMP-1 via the activating receptor NKp30 (45) and sensing of microvesicle-transported parasite RNA via the RIG-I-like receptor MDA5 (46).…”
Section: Introductionmentioning
confidence: 99%